Pengaruh Kecerdasan Emosional Pimpinan terhadap Kinerja Karyawan pada PT. Parangloe Indah - Belo, Sernita Daud; Rasinan, Djusniati; Sambara’, Kordiana (Lembaga Yasin AlSys, 2025)
This study aims to determine the effect of emotional intelligence of leaders on employee performance at PT. Parangloe Indah. Emotional intelligence is measured through self-control, motivation and empathy. While employee performance is measured based on work quality, punctuality and teamwork. The method used in this study is quantitative analysis with data collection techniques through questionnaires distributed to employees of PT. Parangloe Indah. The data obtained were then analyzed using the Spearman correlation coefficient test, the determination coefficient test (r-Square), and the t-test to test the proposed hypothesis. The results of this study indicate that there is a significant positive relationship between emotional intelligence, especially in the form of self-control, and employee performance. In addition, the results of the determination coefficient test indicate that the emotional intelligence variable has a significant effect on employee performance, based on the results of the t-test, emotional intelligence is proven to have a significant effect on employee performance at PT. Parangloe Indah. Thus, it can be concluded that being able to control oneself will have a good impact on employee performance.